Issues of state responsibility before international judicial institutions - Fitzmaurice, Malgosia; Sarooshi, Danesh (Oxford : Hart, 2003)
This text contains papers presented at a high-level conference that was jointly organized by the Institute of Global Law, University College London and the Institute of International Law, Queen Mary, University of London.
Selected conference papers.
Keywords: Government liability (International law) -- Congresses; International courts; Government liability (International law); International courts; state responsibility; international judicial institutions; Conference papers and proceedings